An intramolecular antiparallel G-quadruplex formed by human telomere RNA. Issue 32 (3rd April 2018) - Xiao, Chao-Da; Shibata, Tomokazu; Yamamoto, Yasuhiko; Xu, Yan
Abstract : This is the first report of an antiparallel RNA G-quadruplex formed by a native RNA sequence. Abstract : Until now, RNA G-quadruplexes were believed to only adopt a parallel G-quadruplex structure. In this study, we describe the first observation of an antiparallel RNA G-quadruplex formed by human telomere RNA. This newly described topology is of great interest as it shows that RNA G-quadruplexes can also be polymorphic and adopt structures that are different from the parallel configuration.